Students’ Perception on the Implementation Of Online English Learning in the Covid-19 Pandemic - Prasojo, Niejaar Fatwa; Wahjuningsih, Eka; Andika Hudori, Rizki Febri (EFL Education Journal, 2023)
Abstract This study examines the perceptions of ninth-grade students in a junior high school in Banyuwangi, Indonesia, regarding the implementation of online English learning during the COVID-19 pandemic. Involving 50 students selected through a lottery method, this research focuses on five aspects: technical issues, motivation, time management, social interaction, and teachers’ support and access. The findings indicate that students faced challenges related to technical issues, such as poor internet connectivity and audio/video problems, which disrupted the learning process. Motivation and engagement varied among students, influenced by the absence of face-to-face interaction and distractions in the home environment. Time management was also a concern, with some students struggling to meet the demands of flexible online learning schedules. Limited social interaction and isolation were common experiences, affecting students’ sense of connection and engagement. The lack of access and support from teachers further impacted students’ perceptions of online learning. To sum up, this study underscores the importance of addressing technical challenges, enhancing motivation and engagement, improving time management skills, and fostering social interaction in online English learning. Therefore, further study is suggested to understand the long-term effects of online learning is crucial for identifying gaps and developing targeted interventions. Keywords: perceptions, online English learning, challenges.